Using digital technologies to facilitate social inclusion during the COVID‐19 pandemic: Experiences of co‐resident and non‐co‐resident family carers of people with dementia from DETERMIND‐C19. (13th February 2023) - Hicks, Ben; Gridley, Kate; Dixon, Josie; Baxter, Kate; Birks, Yvonne; Colclough, Carmen; Karim, Anomita; Perach, Rotem; Moseley, Elen; Russell, Alice; Sondh, Harsharon K.; Storey, Bryony; et al.
Abstract: Background: The COVID‐19 pandemic triggered rapid and unprecedented changes in the use of digital technologies to support people's social inclusion. We examined whether and how co‐resident and non‐co‐resident family carers of people with dementia engaged with digital technologies during this period. Methods: Throughout November 2020‐February 2021, we interviewed 42 family carers of people with dementia from our DETERMIND‐C19 cohort. Preliminary analysis was conducted through Framework analysis, followed by an inductive thematic analysis. Findings: Digital technologies served as a Facilitator for social inclusion by enabling carers to counter the effects of the differing restrictions imposed on them so they could remain socially connected and form a sense of solidarity, access resources and information, engage in social and cultural activities and provide support and independence in their caring role . However, these experiences were not universal as carers discussed some C hallenges for tech inclusion, which included preferences for face‐to‐face contact, lack of technological literacy and issues associated with the accessibility of the technology. Conclusion: Many of the carers engaged with Information and Communication Technologies, and to a lesser extent Assistive Technologies, during the pandemic. Whilst carers experienced different challenges due to where they lived, broadly the use of these devices helped them realise important facets of social inclusion as well as facilitated the support they provided to the person with dementia. However, to reduce the 'digital divide' and support the social inclusion of all dementia carers, our findings suggest it is essential that services are attuned to their preferences, needs and technological abilities. Key Points: Many co‐resident and non‐co‐resident carers used Information and Communication Technology and Assistive Technology during the pandemic. The digital technology supported them to retain their social inclusion and manage the care of the person with dementia. Carers faced different challenges when using the digital technology depending on where they lived and on the severity of the person's dementia that they were supporting. Formal services must be attuned to the preferences, needs and technological abilities of carers of people with dementia if they are to address the 'digital divide' and support their social inclusion.